Deconstructing the Binary Tropes of Gender Discrimination in Shazaf Fatima Haider's How It Happened - Ansar, Mohammed; Sami, Muhammad (English Language Education Study Program, Faculty of Social, Economics, and Humanities, University of Nahdlatul Ulama Purwokerto, 2025)
This paper seeks to analyze Shazaf Fatima Haider’s How It Happened using postcolonial feminist framework and through close textual analysis, deconstructing the binarism of gender discrimination in the novel. Women within the traditional patriarchal structures are presented through Dadi’s prescriptive role as she plays in the life of women through putting across structured belief system which dominates women’s existence. Dadi's admonitions, such as the notion that